Exploring possible ways to assist new employees become effective members of Land and Survey Department, Sarawak :an action research study - Ang, Tze How (1998)
This study reviewed the effectiveness of the current orientation programme and explored possible ways to assist new employees become effective members of Land and Survey Department, Sarawak. Thirty-seven respondents from Headquarters, and Kuching and Samarahan divisions who had attended the orientation programme in 1997 answered a questionnaire to evaluate the current orientation programme. Another twenty-three new employees were subsequently selected to attend the module one of the newly designed orientation programme to ascertain its effectiveness. Action research method was employed for this study.